Fruit and seed plumpness, germination and viability of rare plants in Yakutia - D. N. Androsova; N. S. Danilova; K. G. Tkachenko; N. E. Staroverov; A. Yu. Gryaznov (Труды по прикладной ботанике, генетике и селекции)
Background. With the increasing anthropogenic impact on nature, conservation and renewal of rare and endangered plants in natural cenoses is an urgent problem. Quality assessment, identification of full-fledged plump seeds, and determination of their viability is the way to develop reproduction technologies and provide a possibility of repatriating these species to their natural habitats. Collecting and studying natural flora species in botanical gardens helps to save biological resources of useful species and recommend them for urban landscaping.Materials and methods. X-ray techniques were used to analyze seed quality and viability of rare species in the flora of Yakutia: Adonis sibirica Patrin, Phlojodicarpus sibiricus (Steph. ex Spreng.) Koso-Pol., Iris laevigata Fisch. et C.A. Mey., Iris sanguinea Donn, and Paeonia anomala L. Methods developed for the application of microfocus radiography to fruits and seeds were used in the X-ray analysis.Results. Seed quality was assessed according to guidelines. It was shown that fruits and seeds of the studied species developed under the conditions of Yakutia were full-fledged (plump), but due to the presence of a morphophysiological type of dormancy in them, they could germinate only after a cold or multistage stratification.Conclusion. Assessment of reproductive diaspore quality and viability in rare and endangered plant species of Yakutia will make it possible to develop technologies for increasing their seed germination rates and restoring the natural populations of these species.